TANTANGAN MEKANISME TATA KELOLA DATA DALAM MEWUJUDKAN APLIKASI BERSATU LAWAN COVID (BLC) - Nafi'ah, Binti azizatun; Nugroho, Rossi Adi (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2020)
Covid-19 data governance has reached the stage of integrating data into one covid data using ‘Bersatu Lawan Covid’ (BLC) application or the website https://data.covid19.go.id. However, there are many obstacles in its implementation, such as data that is not fully integrated, slow delivery of data from users, user data is not updated, and lack of human resources for data entry. On the other hand, compared to other countries, Indonesia has a low PCR test rate. This paper focuses on finding challenges in the covid-19 data governance mechanism that has been integrated in the BLC application. This type of research is qualitative research, with primary and secondary data collection. Researchers interviewed the public communication sector of the COVID-19 response task force. The results show that the procedural mechanism challenge was to equalize regional and central Covid-19 data by intensifying socialization and mentoring as well as fulfilling human, financial and supporting resources. Meanwhile, the challenge of the relationship mechanism is to grow the willingness of users to report actively every second of the progress of Covid-19 data. We can improvement with strengthening socialization, training, coordination, and fulfilling data entry personnel.